IMPLEMENTASI PEMBELAJARAN JARAK JAUH DENGAN MENGGUNAKAN APLIKASI WHATSAPP SISWA KELAS VI SDN CUMEDAK 02 JEMBER 2020/2021: SDN CUMEDAK 2 JEMBER - LUSIANA SARIYEM (Mitra Pendidikan, 2021)
The outbreak of the corona virus (Covid-19) has felt an impact and has distructed all aspect of life included the education now. The most impact is the long-term effect lost learning in educatio. This aims study is describing the implementation of Distance Learning Using the Whatsapp Application for VI Grade Students in SDN Cumedak 02 Kec. Sumberjambe Kab. Jember 2019/2020. To finding out the effectiveness of distance learning using the WhatsApp application for VI Grade Students in SDN Cumedak 02 Sumberjambe Jember 2019/2020. This type of research is descriptive qualitative research, In this study the subjects were teachers and students of grade VI SD Negeri Cumedak 02 Sumberjambe Jember There were 32 students in the class. In this study Data collection techniques are observation. Questionnaires, and interviews during the distance learning process. Data analysis is used qualitative descriptive to present observation sheets and quantitative to describe the results of interviews with respondents. The results showed that the implementation of learning using the WhatsApp application for grade VI students at SD Negeri Cumedak 02, Sumberjambe Jember was unsuccessful. I It can be concluded that the use of social media can be less effective in online learning for Grade VI.